(untitled) (Revista Espinhaço, 2020)
Aroeira Honey from the North of Minas brought new perspectives of adding value to regional bee production from the possibility of recognition of the Geographical Indication - IG. In this scenario, the article analyzes IG of Honey from Aroeira do Norte de Minas as a social construction, the result of an arrangement involving organizations and institutions that articulate at regional and local level. The empirical research was carried out through the application of a semi-structured questionnaire with representatives of associations, cooperatives and support institutions. The survey results indicate little participation of beekeepers in the discussions and the lack of knowledge about the operationalization of the IG. The top-down IG registration strategy was led by public government entities that operate in the region. The scenario shows that Associations and Cooperatives seek to build new markets for fractionated products with health, organic and IG certifications, in order to obtain better remuneration for the product.